Peranan Audit Internal Dalam Mewujudkan Pelaksanaan Good Corporate Governance Pada Politeknik Negeri Batam - Gita Anadia Maulina; Dwi Kartikasari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
Politeknik Negeri Batam is the only vocational government-owned higher education in the free trade area of Batam, Bintan, and Karimun, in the province of Riau Islands, which must implement Good Corporate Governance in accordance with the established principles and guidelines set by National Committee on Governance Policy (KNKG). Internal audit is one of the elements in Good Corporate Governance and has a role in overseeing management implementation and any practice carried out by the institution. Therefore, this study aims to describe the implementation of Good Corporate Governance in Politeknik Negeri Batam and to know the role of internal audit in realizing the Good Corporate Governance. The analytical method used in this research is descriptive qualitative method with data collected from observation, interviews and documentation. The results of this study is Politeknik Negeri Batam has implemented Good Corporate Governance according to applicable rules. Furthermore, internal audits play an important role in realizing the Good Corporate Governance of Politeknik Negeri Batam.